Restricted carbohydrate diets below 45% energy are not associated with risk of mortality in the National Health and Nutrition Examination Survey, 1999–2018 - Angelotti, Austin; Kowalski, Corina; Johnson, LuAnn K.; Belury, Martha A.; Conrad, Zach (Frontiers in Nutrition, 2024)
Cardiometabolic diseases (CMD) are the leading causes of death for people living in the United States. Dietary strategies, such as restricting carbohydrate intake, are becoming popular strategies for improving health status. However, there is limited and often contradictory evidence on whether restricting carbohydrate intake is related to all-cause, CMD, or cardiovascular disease (CVD) mortality. The objective of the present study was to evaluate the association between restricted carbohydrate diets (<45%en) and mortality from all-causes, CMD, and CVD, stratified by fat amount and class. Data were acquired using the National Health and Nutrition Examination Survey (1999-2018) linked with mortality follow-up until December 31, 2019 from the Public-use Linked Mortality Files. Multivariable survey-weighted Cox proportional hazards models estimated hazard ratios for 7,958 adults (≥20 y) that consumed <45%en from carbohydrates and 27,930 adults that consumed 45-65%en from carbohydrates. During the study period a total of 3,780 deaths occurred, including 1,048 from CMD and 1,007 from CVD, during a mean follow-up of 10.2 y. Compared to individuals that met carbohydrate recommendations (45-65%en), those that consumed carbohydrate restricted diets (<45%en) did not have significantly altered risk of mortality from all-causes (HR:0.98; 95% CI: 0.87, 1.11), CMD (1.18; 0.95, 1.46), or CVD (1.20; 0.96, 1.49). These findings were maintained when the restricted carbohydrate diet group was stratified by intake of total fat, saturated fat (SFA), monounsaturated fat (MUFA), and polyunsaturated fat (PUFA). In conclusion, carbohydrate restriction (<45%en) was not associated with mortality from all-causes, CVD, or CMD. Greater efforts are needed to characterize the risk of mortality associated with varied degrees of carbohydrate restriction, e.g., low (<26%en) and high (>65%en) carbohydrate diets separately.